Racial differences in college-student drinking. Issue 1 (2nd January 2020) - Gardner, Sheena K.; Robertson, Angela A.; Tatch, Andrew; Walker, Courtney S.
ABSTRACT: Racial differences in drinking motives, protective behavioral strategies (PBSs), alcohol consumption, and alcohol-related problems were examined among college student drinkers (N = 443: 296 [66.8%] White, 147 [33.3%] Black). Survey participants were recruited from large undergraduate sociology classes and residence halls at the university. Key differences between Black and White college students in drinking behaviors, reasons for drinking (i.e., motives), and the use of PBSs were observed. These racial differences have implications for the implementation of prevention/intervention programs intending to reduce alcohol consumption and alcohol-related problems among college students.